Ascending aortic aneurysm repair in the setting of Tako-tsubo cardiomyopathy. (May 2021) - Matteucci, Matteo; Ferrarese, Sandro; Corazzari, Claudio; Telli, Gaia; Mantovani, Vittorio; Lorusso, Roberto; Beghi, Cesare
Tako-tsubo cardiomyopathy (TC) is characterized by acute but transient ventricular dysfunction without obstructive coronary artery disease, generally precipitated by emotional and physical triggers. We describe this syndrome in a 76-year-old woman who was admitted with thoracic pain secondary to TC as shown by echocardiographic assessment, with a concurrent diagnosis of giant ascending aortic aneurism. Surgical intervention was delayed to allow ventricular recovery and then to perform ascending aorta replacement. An individualized perioperative approach was applied to avoid a possible TC recurrence with an uneventful postoperative course.